1988
DOI: 10.1051/rphysap:0198800230110182500
|View full text |Cite
|
Sign up to set email alerts
|

Properties of sputtered mercury telluride contacts on p-type cadmium telluride

Abstract: 2014 La valeur élevée du travail de sortie du composé semi-métallique HgTe (q03A6m ~ 5.9 eV) a conduit à utiliser ce matériau pour réaliser des contacts ohmiques de faible résistance spécifique 03C1c (03A9 cm2) sur le composé semi-conducteur II-VI CdTe de type p, dans la gamme des résistivités 70 03A9 cm 03C1B 45 k03A9 cm. Les couches de HgTe ont été déposées par pulvérisation cathodique en atmosphère de mercure à des températures de l'ordre de 150 °C. Les contacts ont été réalisés en technologie planar et leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Janik and Triboulet (1987) 62 showed that HgTe deposited by close space sublimation could provide a low resistance Ohmic contact to CdTe and Hg 1-x Cd x Te, due to good work function matching, but did not fabricate solar cells. This work was extended by Zozime and Vermeulin (1988) 63 to analyze specific contact resistance accounting for doping level. Specific contact resistance remained at 15-500 Ω cm 2 for material of resistivity 1.5-45 kΩ cm but dropped to 7 Ω cm 2 for ~70 Ω cm resistivity material.…”
Section: Mercury Telluride and Hg 1-x CD X Tementioning
confidence: 99%
“…Janik and Triboulet (1987) 62 showed that HgTe deposited by close space sublimation could provide a low resistance Ohmic contact to CdTe and Hg 1-x Cd x Te, due to good work function matching, but did not fabricate solar cells. This work was extended by Zozime and Vermeulin (1988) 63 to analyze specific contact resistance accounting for doping level. Specific contact resistance remained at 15-500 Ω cm 2 for material of resistivity 1.5-45 kΩ cm but dropped to 7 Ω cm 2 for ~70 Ω cm resistivity material.…”
Section: Mercury Telluride and Hg 1-x CD X Tementioning
confidence: 99%
“…In table 3, we present some data for certain materials indicating some discrepancies for the work functions cited, e.g. in [38, 46,47] for metals and for Hg 1-x Cd x Te, which are given in [14,36,37]. The work function for PEDOT:PSS organic contacts used to HgCdTe is relatively high and is equal approximately to 5.2 eV [15].…”
Section: Cr(mo Ti)/hg 1-x CD X Te Contactsmentioning
confidence: 99%
“…tin, chromium, molybdenum, and titanium with their work functions (table 3) should be appropriate ohmic contact metals for all compositions of ntype Hg 1-x Cd x Te and rectifying on p-Hg 1-x Cd x Te. The work function of a MCT semiconductor almost does not depend on its composition and is equal to Φ sc ≈ 5.6-5.9 eV [13,36,37] with an affinity energy χ MCT depending on the chemical composition x (see Exp. 1)).…”
Section: Cr(mo Ti)/hg 1-x CD X Te Contactsmentioning
confidence: 99%